Statins Increase the Frequency of Circulating CD4+FOXP3+ Regulatory T Cells in Healthy Individuals - Ana Lucía Rodríguez-Perea; Carlos J. Montoya; Sven Olek; Claire A. Chougnet; Paula A. Velilla (Journal of Immunology Research)
Statins have been shown to modulate the number and the suppressive function of CD4+FOXP3+ T cells (Treg) in inflammatory conditions. However, it is not well established whether statin could also affect Treg in absence of inflammation. To address this question, eighteen normocholesterolemic male subjects were treated with lovastatin or atorvastatin daily for 45 days. The frequency and phenotype of circulating Treg were evaluated at days 0, 7, 30, and 45. mRNA levels of FOXP3, IDO, TGF-β, and IL-10 were measured in CD4+ T cells. We found that both statins significantly increased Treg frequency and FOXP3 mRNA levels at day 30. At day 45, Treg numbers returned to baseline values; however, TGF-β and FOXP3 mRNA levels remained high, accompanied by increased percentages of CTLA-4- and GITR-expressing Treg. Treg Ki-67 expression was decreased upon statin treatment. Treg frequency positively correlated with plasma levels of high-density lipoprotein cholesterol (HDL-c), suggesting a role for HDL-c in Treg homeostasis. Therefore, statins appear to have inflammation-independent immune-modulatory effects. Thus, the increase in Treg cells frequency likely contributes to immunomodulatory effect of statins, even in healthy individuals.